2010
DOI: 10.1292/jvms.09-0386
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Susceptibility Artifacts and Tissue Injury Caused by Implanted Microchips in Dogs on 1.5T Magnetic Resonance Imaging

Abstract: ABSTRACT. Performing magnetic resonance imaging (MRI) in patients with a metallic implant raises concern over the potential complications, including susceptibility artifacts, implant migration, and heat injury. The purpose of this study was to investigate these complications in dogs with implanted microchips by evaluating MR images and the histopathological changes after 1.5 Tesla (T) MRI. Five dogs underwent microchip implantation in the cervicothoracic area. One month later, the area was imaged using 1.5T MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 20 publications
2
23
0
5
Order By: Relevance
“…Thus, individuals are improvising their own insideables and internet of the body as large organizations promote wearables and the internet of things. This practice has emerged from recognition among its pioneers that the new practice of implanting microchips into pets could be transferred easily to human beings [90,91]. Such improvised DIY practices can suddenly start and spread to bring erratic non-linear interactions with top-down planned systems.…”
Section: Propositionmentioning
confidence: 99%
“…Thus, individuals are improvising their own insideables and internet of the body as large organizations promote wearables and the internet of things. This practice has emerged from recognition among its pioneers that the new practice of implanting microchips into pets could be transferred easily to human beings [90,91]. Such improvised DIY practices can suddenly start and spread to bring erratic non-linear interactions with top-down planned systems.…”
Section: Propositionmentioning
confidence: 99%
“…There are several ways in which the MRI scanner and the microtransponder might interact: for example, the magnetic forces or the radio waves involved in each technology may interfere with one another. Deterioration of image quality due to susceptibility of artifacts, movement of microchips, and the heating of the transponder is documented . The technical components of the transponder could be damaged by heating.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature increases as high as 25°C in a brain stimulation implant (1.5 Tesla), 48°C in intravascular guidewires (1.5 Tesla), 63°C in a cardiac‐pacing electrode (1.5 Tesla), and 64°C in an intracranial pressure transducer (3 Tesla) have been reported. Recent studies have looked for alteration in function of identification microchips in 1.0 (41 dogs; 53 dogs) and 1.5 Tesla MR scanners (three dogs) . The results showed that under the practical conditions of a routine MR study, the identification number allocated on the implanted microchips was displayed correctly.…”
Section: Introductionmentioning
confidence: 99%
“…Various publications have reported advanced imaging susceptibility artifacts as well as techniques to reduce these artifacts . In a recent case report, a brown‐pigmented intraorbital prosthetic caused a significant susceptibility artifact on MR images that precluded adequate visualization of intracranial structures in a patient with neurologic disease .…”
Section: Introductionmentioning
confidence: 99%
“…1 Various publications have reported advanced imaging susceptibility artifacts as well as techniques to reduce these artifacts. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In a recent case report, a brown-pigmented intraorbital prosthetic caused a significant susceptibility artifact on MR images that precluded adequate visualization of intracranial structures in a patient with neurologic disease. 18 Since this publication, to the authors' knowledge, no studies have evaluated the effects of other commonly used intraorbital prosthetics on MRI or CT images or potential techniques to reduce this artifact.…”
Section: Introductionmentioning
confidence: 99%